Response characterization of an Y2O3:Eu-based radioluminescence probe under 60Co irradiation - Molina, Pablo Fernando (2013)
In this work the feasibility of using Y2O3:Eu as a fiberoptic dosimetry (FOD) probe for real-time dosimetry has been investigated for the first time. In particular, the stability of the radioluminescence (RL) signal after repeated use and RL emission spectrum of a Y2O3:Eu-based fiberoptic probe have been determined. The probe has been also used to obtain a percentage depth dose curve (PDD) in a water phantom under 60Co irradiation, and its performance has been compared to that of a standard ionization chamber.